Bilateral Hydronephrosis and Cystitis Resulting from Chronic Ketamine Abuse - Vu Huy Tran; Mathew Nelson; Joshua Nogar; Robert M. Bramante (Western Journal of Emergency Medicine, 2014)
Ketamine associated urinary dysfunction has become increasingly more common worldwide. Point-of-care ultrasound (POCUS) is an established modality for diagnosing hydronephrosis in the emergency department. We describe a case of a young male ketamine abuser with severe urinary urgency and frequency in which POCUS performed by the emergency physician demonstrated bilateral hydronephrosis and a focally thickened irregular shaped bladder. Emergency physicians should consider using POCUS evaluate for hydronephrosis and bladder changes in ketamine abusers with lower urinary tract symptoms. The mainstay of treatment is discontinuing ketamine abuse. [West J Emerg Med. 2014;15(4):382-384.]